2016
DOI: 10.1172/jci87492
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell desensitization inhibits calcium flux and aberrantly remodels actin

Abstract: Rush desensitization (DS) is a widely used and effective clinical strategy for the rapid inhibition of IgE-mediated anaphylactic responses. However, the cellular targets and underlying mechanisms behind this process remain unclear. Recent studies have implicated mast cells (MCs) as the primary target cells for DS. Here, we developed a murine model of passive anaphylaxis with demonstrated MC involvement and an in vitro assay to evaluate the effect of DS on MCs. In contrast with previous reports, we determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 51 publications
(63 reference statements)
3
92
0
1
Order By: Relevance
“…Future experiments are needed to determine intrinsic cellular changes in subjects actively undergoing immunotherapy in addition to the plasma changes observed in these studies. For example, we have previously demonstrated impaired calcium flux due to actin rearrangement following desensitization in model systems . The findings also assist in the understanding of the changes that distinguish subjects that develop SU.…”
Section: Discussionmentioning
confidence: 62%
“…Future experiments are needed to determine intrinsic cellular changes in subjects actively undergoing immunotherapy in addition to the plasma changes observed in these studies. For example, we have previously demonstrated impaired calcium flux due to actin rearrangement following desensitization in model systems . The findings also assist in the understanding of the changes that distinguish subjects that develop SU.…”
Section: Discussionmentioning
confidence: 62%
“…This in vitro model of rapid MCs/IgE DS protocol has been reproduced in many studies and has consistently shown the inhibition of all of the MC activation hallmarks (Figure 3 and Figure 4) [45,53,54]. As shown in Figure 3 and Figure 4, compared to activated cells, desensitized cells had a diminished immediate release of β-hexosaminidase (Figure 3a), early and late TNF-α (Figure 3b), IL-6 production (Figure 3c), de novo synthesis of lipid mediators (Figure 3d), and calcium flux (Figure 3e) [53].…”
Section: Molecular Mechanisms In Ige Mast Cell Desensitizationmentioning
confidence: 98%
“…This demonstrates that the mechanism of DS is an antigen-specific process and does not disable the IgE bounded FcεRI receptor for other antigens [45]. …”
Section: Molecular Mechanisms In Ige Mast Cell Desensitizationmentioning
confidence: 99%
“…At the cellular level, there have been a number of studies of desensitization using both basophil and mast cell models . Emphasis has been placed on determining whether subthreshold dosing of the cells in vitro mimics the process observed in vivo.…”
Section: Introductionmentioning
confidence: 99%